Characterization of microbial siderophores by mass spectrometry - Pluháček, Tomáš; Lemr, Karel; Ghosh, Dipankar; Milde, David; Novák, Jiří; Havlíček, Vladimír (Mass spectrometry reviews, 2016)
Siderophores play important roles in microbial iron piracy, and are applied as infectious disease biomarkers and novel pharmaceutical drugs. Inductively coupled plasma and molecular mass spectrometry (ICP-MS) combined with high resolution separations allow characterization of siderophores in complex samples taking advantages of mass defect data filtering, tandem mass spectrometry, and iron-containing compound quantitation. The enrichment approaches used in siderophore analysis and current ICP-MS technologies are reviewed. The recent tools for fast dereplication of secondary metabolites and their databases are reported. This review on siderophores is concluded with their recent medical, biochemical, geochemical, and agricultural applications in mass spectrometry context.
Keywords: antibiotická rezistence; biodegradace; Biodegradation, Environmental; chelátory; iron; Mass Spectrometry; Secondary Metabolism; Microbial Sensitivity Tests; siderofory; sekundární metabolismus; Chelating Agents; mass spectrometry; dereplication; siderophores; Drug Resistance, Microbial; mikrobiální testy citlivosti; biomarkers; spektrofotometrie atomová; hmotnostní spektrometrie; Spectrophotometry, Atomic; Siderophores